A net present worth analysis of considered academic programs at a private, regional higher education institution - Doss, Daniel A.; Jones, Don Wayne; Sumrall, William; Henley, Russ; McElreath, David; Lackey, Hilliard; Gokaraju, Balakrishna (Journal of Interdisciplinary Studies in Education, 2015)
This paper examines the situation of a private, liberal arts college that sought to enhance its competitiveness by investigating the financial potential and viability of offering either a complete human resources degree program or a graduate certificate with an emphasis area in human resources as a method of bolstering its strategic position within its academic market. The net present worth (i.e., net present value) method was the analytical method of financial analysis. The net present worth outcomes indicated that the complete degree program was the preferred alternative.